Implementation of Pharmaceutical Drug Traceability Using Blockchain Technology - Mohana, Muniandy; Ong, Gabriel, Tze Ern (INTI International University, 2019)
The healthcare industry relies heavily on the use of pharmaceutical drugs to treat patients, and acquires said drugs using supply chain management. However, fraud and abuse cases in current healthcare industry are a major problem, costing the industry billions of dollars annually. Furthermore, counterfeit drugs also plague the healthcare industry, which is a major health concern to patients who consume said drugs. To solve these problems, a system is required to trace pharmaceutical drugs as they travel the supply chain, from the provider of the ingredients to produce pharmaceutical drugs, to its consumers. The proposed project will implement blockchain, an emerging technology that enables decentralized storage of data and immutable data. Blockchain stores data in a distributed ledger visible to all participants, which will create transparency in the supply chain, a much-needed change, which are presently very complex and opaque. Blockchain records the transaction details of relevant participants involved in the supply chain process as pharmaceutical drugs move through the supply chain.